1936
DOI: 10.1177/003591573602901207
|View full text |Cite
|
Sign up to set email alerts
|

The Endocrine Control of the Prostate

Abstract: The Endocrine Control of the Prostate By S. ZUCKERMAN BEIT MEMORIAL RESEARCH FELLOW (Fromi the Department of Humnan Anatomy, Oxfordl) FROM the turn of the present century until some five or six years ago, the prostate was an organ whose physiology was little discussed and even less investigated, and whose departures from the normal were events to be treated only by direct surgical methods. Within the past few years, facts about the endocrinology of this organ have multiplied so fast as to suggest a revision of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1937
1937
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
(8 reference statements)
1
11
0
Order By: Relevance
“…The Skoptzys, a Russian sect in which the males underwent ritual castration at 35 years did not suffer from prostatic enlargement (Zuckerman, 1936). Furthermore, it has been shown that the absence of testicular function from a young age, either from castration or hypopituitarism, prevents the occurrence of BPH in men living into the over 55 age group.…”
Section: Benign Prostatic Hyperplasia (Bph)mentioning
confidence: 99%
“…The Skoptzys, a Russian sect in which the males underwent ritual castration at 35 years did not suffer from prostatic enlargement (Zuckerman, 1936). Furthermore, it has been shown that the absence of testicular function from a young age, either from castration or hypopituitarism, prevents the occurrence of BPH in men living into the over 55 age group.…”
Section: Benign Prostatic Hyperplasia (Bph)mentioning
confidence: 99%
“…Aside from the work of Vesalius, an early description of the mammalian accessory sex glands was reported by Gerard Blasius in his treatise on comparative anatomy, which was published in 1674 and described simply as “glandulae” surrounding the neck of the bladder (Cole, 1949). At about the same period the importance of the clinical perspective was being developed through the observation by Samuel Collins that prostate enlargement caused bladder neck obstruction (Zuckerman, 1936). This was further established in the 18th century by Giambattista Morgagni, the founder of modern pathology (Franks, 1954).…”
Section: A History Of Prostate Anatomymentioning
confidence: 99%
“…In 1786 he wrote that ''The prostate and Cowper's glands, and those of the urethra, which in the perfect male are soft and bulky, with a secretion salt to the taste, in the castrated animal are small, flabby, tough and ligamentous, and have little secretion.' ' Zuckerman (1936) points out the notable fact that even though the inference of the observation would suggest that castration might be considered a treatment for the relief of prostate enlargement, the therapeutic value was not considered until almost a century later. The current understanding of prostate development and anatomy progressed through the publication of new findings each decade over the past century (Pallin, 1901;Lowsley, 1912;Johnson, 1920;Price, 1936;LeDuc, 1939;Huggins and Webster, 1948;Gil Vernet, 1953;McNeal, 1968McNeal, , 1978McNeal, , 1983Timms et al, 1994).…”
Section: A History Of Prostate Anatomymentioning
confidence: 99%
“…Control hosts were sacrificed on the day of castration. Experimental hosts were sacrificed at 13 different time points (post-castration day 1,2,3,4,5,7,8,9,10,14,17,18,21). Immediately following sacrifice, prostatic samples (grafts) were harvested.…”
Section: Experimental Designmentioning
confidence: 99%